Efektivitas Kahoot terhadap Hasil Belajar Kalimat Langsung dan Tidak Langsung pada Kelas V SD - Aisyah Putri Primadini; Fariz Nurfan Gandhi; Ika Dian Rahmawati (Educatio, 2026)
This study aims to evaluate the effectiveness of using Kahoot as a learning media in improving students’ learning outcomes on direct and indirect sentences in Grade V of SDN Banyuajuh 3. The research employed a quantitative approach with a quasi-experimental method using a pre-experimental design, specifically a One-Group Pretest-Posttest Design. The participants consisted of 30 fifth-grade students selected through a saturated sampling technique. Data were collected using a multiple-choice test consisting of 20 questions and interviews with the classroom teacher. The findings showed a significant improvement, indicated by the average pretest score of 41.67, which increased to 80.10 in the posttest. The learning mastery level also improved from 13.33% to 96.67%. The interview results revealed that Kahoot was able to increase students’ motivation and participation in the learning process. Therefore, Kahoot is proven to be effective in improving students’ learning outcomes on direct and indirect sentences at the elementary school level.